Pelatihan Penyusunan Laporan Keuangan dan Manajemen Keuangan UMKM dalam Upaya Pengembangan Usaha - Facrul Rozi; Mekar Meilisa Amalia; Nurhayati Nurhayati Nurhayati; Sahnan Rangkuti; Dewi Wahyuni (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Since the government ratified the Indonesian batik day, efforts to develop the business of batik craftsmen in Solo Raya have generally increased, however, the craftsmen have experienced difficulties in loan business. Creditors need financial statements which are the only reliable information in consideration for lending. Not infrequently because batik craftsmen throughout Solo Raya do not have financial reports, the craftsmen have not been able to get business capital from loans. The approach used in this Abdimas activity: 1). Lecture method. 2) Training Methods. Meanwhile, the data collection method used by the Abdimas Team on Financial Management is in the form of questions and answers and discussions with participants. Overall, counseling on the preparation of financial reports and financial management of MSMEs received a good response from various parties, both the perpetrators of MSMEs in Wijaya Kusuma batik, batik craftsmen and officials in Solo Raya.